Improvements in Al-Qur'an Letter Reading for Children with Minor Mental Disabilities Using the Bil Hikmah Methods - Lidra Agustina Tanjung; Amiruddin Siahaan; Aidil Ridwan Daulay; Fiki Robi Handoko Harahap; Maharani Sartika; Muhammad Hafiz; Sabila Akbar; Vera Yunita Siregar; Muhammad Azhar (Jurnal Basicedu, 2023)
Al-Qur'an is primary literacy for Muslims, including elementary age children. Likewise, for mentally retarded children the ability to read the Koran still leaves its own problems. This study aims to describe efforts to improve the ability to read the letters of the Qur'an for children with mild mental retardation through the bil hikmah method. The setting of this research was in Class VII C of the Batubara State SLB, where in this class there were three mild mentally retarded children with the initials MRF, ZM and K with different characteristics. The research will be conducted using classroom action research methods. This research was conducted in collaboration with teachers. This research was conducted in 2 cycles. Each cycle starts from the stages of planning, implementing actions, observing and reflecting. The results of the research are described in narrative and graphical form from the process to the improvement results in cycle II. In the first cycle the children obtained MRF and ZM results of 65% and K 60% and the results in the second cycle of MRF, ZM and K were 85%. This shows that the bil Hikmah method is effectively used to improve the ability to read Al-Quran letters for children with mild mental retardation.